Comparison of immunofluorescence and enzyme immunoassay for detection of measles-specific immunoglobulin M antibody. - Rossier, E (1991)
During a measles outbreak, 283 serum specimens from 221 suspected cases of measles were tested by immunofluorescence and enzyme immunoassay for the presence of measles-specific immunoglobulin M (IgM) antibodies by using commercially available reagents. There was 97% agreement between the two assays; thus, the choice of the method for diagnostic testing is a matter of convenience and experience. In all 62 cases of measles from which a single blood sample was available, measles IgM-specific antibodies were detectable by both methods. Fifty percent of the 62 cases were positive within 3 days after onset of the rash. This increased to 91% 10 days after onset of the rash.